Bibliometric and Visualized Analysis of 2011–2020 Publications on Physical Activity Therapy for Diabetes - Huang, Keke; Zhu, Jing; Xu, Shaozhe; Zhu, Rong; Chen, Xi (Frontiers in Medicine, 2022)
Background: This study was designed to investigate the global emerging trends of physical activity therapy for diabetes based on a bibliometric analysis of the publications. Methods: Publication papers from 2011 to 2020 were retrieved from the database of “Web of Science Core Collection” with the topic search. The number of papers, citations, authors, countries, institutions, and references were extracted. CiteSpace was used to analyze co-citation on authors, collaborations between countries and institutions, and detected the emerging trends of burst keywords and references. Results: A total of 2,351 publications were recruited in this study, and showed an upward trend of annual publications. Diabetes obesity & metabolism (journal), the United States (country), Harvard University (institution) and Kaku K (author) published the most papers in this research field. “impaired glucose tolerance”(2011-2012) was the highest strength burst keyword, while “cardiovascular outcome” (2017–2020) was the most burst keyword last 5 years. Moreover, “Standards of medical care in diabetes—2014” was the strongest burst reference. Conclusions: “Physical activity therapy for diabetes” has been accepted remarkably over the last 10 years. The keywords of “impaired glucose tolerance”, “Cardiovascular outcome“， “improves glycemic control”, “Self-management”, and exercise type including “Aerobic exercise, muscle strength” may be the latest research frontiers.